2008
DOI: 10.1158/1078-0432.ccr-07-1823
|View full text |Cite
|
Sign up to set email alerts
|

Unique Cell Surface Expression of Receptor Tyrosine Kinase ROR1 in Human B-Cell Chronic Lymphocytic Leukemia

Abstract: Purpose: Gene expression profiling identified receptor tyrosine kinase ROR1, an embryonic protein involved in organogenesis, as a signature gene in B-cell chronic lymphocytic leukemia (B-CLL). To assess the suitability of ROR1 as a cell surface antigen for targeted therapy of B-CLL, we carried out a comprehensive analysis of ROR1protein expression. Experimental Design: Peripheral blood mononuclear cells, sera, and other adult tissues from B-CLL patients and healthy donors were analyzed qualitatively and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
250
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(272 citation statements)
references
References 37 publications
12
250
0
5
Order By: Relevance
“…3,4 In agreement with these studies, we identified the HLA-B*07:02-restricted ROR1 peptide NPRYPNYMF as a component of the HLA ligandome of CLL samples (Figure 1 A,B and Online Supplementary Table S1). In contrast, the ROR1 peptide could not be found in the HLA ligandome of normal cells (data not shown).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…3,4 In agreement with these studies, we identified the HLA-B*07:02-restricted ROR1 peptide NPRYPNYMF as a component of the HLA ligandome of CLL samples (Figure 1 A,B and Online Supplementary Table S1). In contrast, the ROR1 peptide could not be found in the HLA ligandome of normal cells (data not shown).…”
supporting
confidence: 83%
“…It has been demonstrated that ROR1 messenger Ribonucleic Acid (mRNA) is highly expressed in CLL cells (Online Supplementary Figure S1) and a uniform expression of ROR1 protein is detected on their cell surface. 3,4 In contrast, ROR1 expression was not found in other blood cells or on bone marrow-derived cells, except on a small subset of precursor B cells.…”
mentioning
confidence: 91%
“…Other targets identified in patients with ALL were ROR1, N-RAS, and CSF1R. Interestingly, overexpression of ROR1 has been observed in several studies of lymphocytic malignancies (30,31). Also, we identified JAK2 and EPHA5 as targets in patients with CMML, and FLT1, EPHA4, PDGFR␣/␤, PTK2B, FYN, and JAK1/3 in patients with AML.…”
Section: Rapid Functional Screening Of Patients With Hematologic Malimentioning
confidence: 50%
“…However, if researchers are to better examine the role of cellular elastic and viscoelastic properties in vivo, primary cancer cells as well as their normal counterparts must be isolated for tests. Recent studies of primary cancerous B lymphocytes have shown that the receptor tyrosine kinase-like orphan receptor 1 (ROR1) is selectively expressed on the surface of B-cell chronic lymphocytic leukemia and on some B-cell lymphomas (including mantle cell lymphoma, marginal zone lymphoma, and follicular lymphoma), whereas normal B lymphocytes and other normal cells do not express ROR1 (Baskar et al, 2008;Bicocca et al, 2012). Hence, ROR1 is a suitable marker for isolating cancerous B lymphocytes from lymphoma patients.…”
Section: Rusults and Discussionmentioning
confidence: 99%